Increasing the efficiency and productivity in the production of low voltage switchboard using resource constrained project scheduling - Hendy Tannady; Yona Maimury (Journal of Industrial Engineering and Management (JIEM), 2018)
Purpose: This research was made with the aim to give a scheduling proposal for the assembly activity and the proposal to allocate those activities into available resources using the resource-constrained project scheduling. Design/methodology/approach: The research begins with the problem exposition in the existing system on the Assembly Department of panel manufacturer company. To overcome the problem, several scheduling alternatives are formulated to yield better productivity. The performance of proposed system using RCPS is assessed using simulation method. Considering the circumstance of demand rate, the scenarios chosen are based on the parameter such as product departure cycle time, resource utilization, product ouput, and number of resource required. Findings: The scheduling alternatives provides the better arrangement of work elements in the assembly activity, especially for the product that represent the highest demand rate. For further research, the paper gives encouragement so that the application of RCPS can be used broader in the manufacturing area. Research limitations/implications: Although the findings was addressed to improve the existing system on the Assembly Department, the practical application haven't been undergone and the performance assessment only based on the simulation method. Practical implications: By implementing the proposed scheduling, the company will experience several benefits. First, the company could increase its productivity by better utilization of its resources. Second, based on the simulation result, the company could avoid the backorder option while dealing with the high demand rate, and even can fully maximize its resource utilization without adding more worker or apply the overtime policy. Finally, the proposed scheduling that converted into the work instruction could help the company to perform the knowledge transfer from the existing worker or resigned worker to the newly-hired worker. Originality/value: The outcome of the research could become the guidance for other companies which have similar assembly system to apply the same method. This is the best paper that represents the application of RCPS in the large-sized component assemblies, where the walking worker is responsible for carrying tasks to each unmoved unit.
Keywords: 650; resource-constrained project scheduling; made-to-order; ACTIM; ACTRES; TIMERES; assembly system; simulation